## kenneyfamily 3 years ago What is the difference between an arithmetic and geometric sequence?

1. Rohangrr

Arithmetic formula: \[ t_n = t_1 + (n - 1)d \] \[t_n \] is the nth term, \[t_1 \] is the first term, and d is the common difference

2. Rohangrr

Geometric formula: \[ t_n = t_1 . r^(n - 1) \] \[t_n \] is the nth term, \[t_1 \] is the first term, and r is the common ratio.

3. Rohangrr

Did you get the concept @kenneyfamily

4. kenneyfamily

yes!

5. shruti

Arithmetic sequences have a constant difference between terms: 1, 3, 5, 7,... The difference between successive terms is 2. The general formula for the nth term is a(n) = a(1) + d·(n-1) where a(1) = the initial term , d = difference between terms. So to find the 5th term (which we can see in the sequence should be 9), we plug in n = 5 a(5) = 1 + 2·(5-1) = 1+2·4 = 9 WHEREAS Geometric sequences have a constant ratio between terms: 2, 6, 18, 54, ... The ratio between successive terms is 3. The general formula for the nth term is a(n) = a(1)·r^(n-1), where a(1) is the first term and r is the ratio. So to find the 5th term (which we can see in the sequence should be 162), we plug in n = 5 EXAMPLE.. a(5) = 2·3^(5-1) = 2·3^4 = 2·81 = 162

6. angela210793

arithmetic sequence is a sequence of numbers such tht the difference of two condegutive numbers is a constant|dw:1341738867627:dw| geometirc sequence is a sequence of numbers such tht the quotient between two consegutive numbers is a constant|dw:1341739044301:dw|

7. Rohangrr

if more Arithmetic sequences have a constant difference between terms: 1, 3, 5, 7,... The difference between successive terms is 2. The general formula for the nth term is a(n) = a(1) + d·(n-1) where a(1) = the initial term, d = difference between terms. So to find the 5th term (which we can see in the sequence should be 9), we plug in n = 5 a(5) = 1 + 2·(5-1) = 1+2·4 = 9 Geometric sequences have a constant ratio between terms: 2, 6, 18, 54, ... The ratio between successive terms is 3. The general formula for the nth term is a(n) = a(1)·r^(n-1), where a(1) is the first term and r is the ratio. So to find the 5th term (which we can see in the sequence should be 162), we plug in n = 5 a(5) = 2·3^(5-1) = 2·3^4 = 2·81 = 162

8. kenneyfamily

AWESOME GUYS...THANK YOU SO MUCH!!! :)

9. angela210793

did u guys copy=pasted the same thing O.o

10. TransendentialPI